1996
DOI: 10.1016/0014-5793(95)01468-3
|View full text |Cite
|
Sign up to set email alerts
|

The TRH‐like peptides in rabbit testis are different from the TRH‐like peptide in the prostate

Abstract: Human seminal fluid contains a number of tripeptide amides with similar structures to thyrotropin releasing hormone (TRH), two of which have been identified as pGlu-Glu-Pro amide and pGlu-Pbe-Pro amide. To determine whether these peptides originate in the same tissues and have the same molecular origin, TRH-immunoreactive peptides were extracted from the prostate and testis of the rabbit, purified by ion exchange chromatography and HPLC, and identified by co-chromatography with 3H-labelled marker peptides. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…1,13) and cross-react, to varying extents, with antisera raised against TRH (6, 14 -16). In human prostate and seminal fluid ϽEQP-NH 2 and ϽEFP-NH 2 have been identified (17)(18)(19), whereas ϽEYP-NH 2 has been found in alfalfa (20). Another TRH-like peptide is ϽEEP-NH 2 , which has been detected in pituitary, prostate, and seminal fluid of various mammalian species (including man, rat, and rabbit) (7,8,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…1,13) and cross-react, to varying extents, with antisera raised against TRH (6, 14 -16). In human prostate and seminal fluid ϽEQP-NH 2 and ϽEFP-NH 2 have been identified (17)(18)(19), whereas ϽEYP-NH 2 has been found in alfalfa (20). Another TRH-like peptide is ϽEEP-NH 2 , which has been detected in pituitary, prostate, and seminal fluid of various mammalian species (including man, rat, and rabbit) (7,8,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…An N-extended form of TRH-like peptides was observed in substantial concentration in human plasma (Ruiz-Alcaraz and del Rio-Garcia 2003) or in human semen (Khan and Smyth 1993). The analysis of rabbit prostate and testis have shown that in contrast to the prostate, testis contains high concentrations of N-extended form of pEFPam, but essentially no tripeptide (Linden et al 1996). Similar results were found in human testis and prostate (Bilek et al 1994).…”
Section: Introductionmentioning
confidence: 71%
“…Although it was initially suggested that TRH-like peptides, other than TRH, were not detectable in brain (Rondeel et al, 1995a;Rondeel et al, 1995b), it was later shown that, among other, Gln-Tyr-Pro-NH 2 , and Gln-Phe-Pro-NH 2 are present in brain (Pekary et al, 2004;Pekary et al, 2005). To our knowledge, although these peptides are likely the product of posttranslational processing of precursor peptides (Linden et al, 1996), the precursors are still unknown. However, they may act as intercellular messengers, including in the brain, since their concentrations can vary rapidly in response to some stimuli, suggesting changes in synthesis and/or release (Pekary and Sattin, 2012;Pekary et al, 2015), and there is direct evidence that a peptide similar to Gln-Phe-Pro-NH 2 can be released into hypothalamic extracellular space in vitro (Meńdez et al, 1999).…”
Section: Trhde Gene Transcripts Protein Structure Isoforms and Spementioning
confidence: 95%